Cotton production in the Yellow River Basin of China: reforming cropping systems for ecological, economic stability and sustainable production - Yuexia Su; Xuewen Wei; Xuewen Wei; Xuewen Wei; Xuewen Wei; Zhanbiao Wang; Zhanbiao Wang; Lei Gao; Lei Gao; Zhenggui Zhang; Zhenggui Zhang (Frontiers in Sustainable Food Systems)
Cotton cropping systems are critical for ensuring the stability and sustainability of cotton production, which is of vital importance to both the agricultural and economic sectors of China. This review examines the historical evolution, challenges, and potential reforms of cotton cropping systems in Shandong Province, a key cotton-producing region in China. The study highlights the effects of economic, technological, and ecological factors on cotton production in the region, emphasizing the importance of optimizing cotton cropping systems to stabilize production, enhance efficiency, and promote rural revitalization. Based on empirical evidence, the review suggests several innovative approaches, including advanced cotton cultivation systems and large-scale mechanization, designed to enhance the sustainability of cotton farming. Furthermore, the research highlights the critical need to balance cotton cultivation with national food security goals by addressing the challenges of saline and alkaline soils and promoting sustainable cotton industry development in the Yellow River Basin; it further offers forward-looking policy recommendations for Shandong, advocating for the integration of advanced agricultural technologies, the establishment of robust agricultural insurance systems, and the implementation of region-specific strategies to ensure both ecological resilience and economic viability—ultimately positioning cotton farming as a key driver of rural revitalization and green development. The findings of this study provide valuable insights for policy-making, guiding the sustainable development of cotton farming in Shandong and other regions with similar requirements.